2009
DOI: 10.1117/1.3257254
|View full text |Cite
|
Sign up to set email alerts
|

Physiological fluorescence lifetime imaging microscopy improves Förster resonance energy transfer detection in living cells

Abstract: Abstract. Accurate, unambiguous detection of molecular interactions in living cells via measurements of Förster ͑or fluorescence͒ resonance energy transfer ͑FRET͒ events is experimentally challenging. We develop and apply a physiological fluorescence lifetime imaging microscopy ͑physiological FLIM͒ system to significantly improve FRET detection in living cells. Multiple positive and negative cellular controls are implemented to validate the experimental method developed. FLIM measurement techniques were found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 12 publications
(16 reference statements)
0
15
0
Order By: Relevance
“…Consistent with our previous studies, SF irradiation led to retraction of the severed ends of the targeted SF (top row), and inspection of the donor and FRET intensity (middle rows) revealed that the VinTS localizes to FAs as expected. Because the FRET intensity also depends on factors unrelated to donoracceptor separation (Chang and Mycek, 2012;Chang et al, 2007;Chang et al, 2009;Zhong et al, 2007), such as the amount of localized VinTS, we created FRET ratio maps in which we masked the FRET intensity to show only FAs and normalized this intensity by the donor intensity (bottom row). In these maps, an increasing FRET ratio corresponds to an increasing FRET signal (actual degree of energy transfer) or decreasing tension, which can in turn be tracked on an FA-by-FA basis.…”
Section: Mapping Tension Distributions Of Single Stress Fibersmentioning
confidence: 99%
“…Consistent with our previous studies, SF irradiation led to retraction of the severed ends of the targeted SF (top row), and inspection of the donor and FRET intensity (middle rows) revealed that the VinTS localizes to FAs as expected. Because the FRET intensity also depends on factors unrelated to donoracceptor separation (Chang and Mycek, 2012;Chang et al, 2007;Chang et al, 2009;Zhong et al, 2007), such as the amount of localized VinTS, we created FRET ratio maps in which we masked the FRET intensity to show only FAs and normalized this intensity by the donor intensity (bottom row). In these maps, an increasing FRET ratio corresponds to an increasing FRET signal (actual degree of energy transfer) or decreasing tension, which can in turn be tracked on an FA-by-FA basis.…”
Section: Mapping Tension Distributions Of Single Stress Fibersmentioning
confidence: 99%
“…24 In addition, this system had a large temporal dynamic range ͑750 ps to ϱ͒, 50 ps lifetime discrimination, and spatial resolution of 1.4 m, which made it very suitable for studying a variety of endogenous and exogenous fluorophores in biological samples. 2,4,[25][26][27][28] Fluorescence lifetime maps were determined by first acquiring fluorescence intensity images at four delays and then calculating the lifetime values from the intensity images on a pixel-by-pixel basis ͑described in Sec. 3.2͒.…”
Section: Time-gated Flimmentioning
confidence: 99%
“…1 However, low fluorescence signals from biological samples can be a challenge, causing poor lifetime precision, and this will affect, to a great extent, the quantitative applications of FLIM, such as the detection of Förster resonance energy transfer for molecular interactions and the sensing of fluorophore microenvironments. [2][3][4][5] When endogenous fluorophores are imaged, low fluorescence signals may result from low intrinsic fluorophore concentrations and/or unfavorable optical properties of fluorophores ͑e.g., fluorescence excitation and emission wavelengths, quantum yield, photobleaching rate͒. When exogenous fluorophores are imaged, low signals can result from the low fluorophore concentrations that are required to minimize effects on sample physiology and/or from the low transfer efficiency of fluorophores/fluorophore precursors ͑genes or different forms of fluorophores͒ from extracellular media into live cells.…”
Section: Introductionmentioning
confidence: 99%
“…The detection and resolution limit depends on many variables. 1,6,7,36,38 We are certain that for any given system, the use of multiple, rather than single, acceptors will enhance the transfer efficiency and allow for larger distances to be measured. There are also several commercially available reactive Near Infra Red probes that can be used to create a R 0 of about 80 to 85 Å.…”
Section: Discussionmentioning
confidence: 99%
“…For larger donor-acceptor separations, potential artifacts and errors that are typically present in experiments can easily overwhelm the expected effects, especially when employing cellular microscopy. 6,7 Recently available reactive forms of far-red probes with both high extinction coefficients and good quantum yields can extend the practical R 0 to about 80 Å and the observation window to around 110 to 120 Å. 8,9 Presently, one typically labels specific sites using a single donor on a given macromolecule and a single acceptor on another macromolecule in order to monitor intermolecular distances during interactions (e.g., physiological processes).…”
mentioning
confidence: 99%